Sustainable development and its relationships with other directions of the development of European Union countries - Cheba, Katarzyna; Bąk, Iwona (Zrównoważony rozwój i jego związki z innymi kierunkami rozwoju krajów Unii Europejskiej, 2020)
The main purpose of the paper is to present proposals for the study of relationships between the dimensions of sustainable development and other areas of the EU countries’ development: innovation and competitiveness both from theoretical and practical perspective. The first part presents the assumptions adopted by the authors, and the second the 2-stage research procedure. In the first stage, the relative taxonomic measure of development was calculated, while in the next one the correlation coefficients between considered dimensions and areas were calculated. According to the authors, in the studies of relationships between sustainable development and other considered areas, one should take into account all of the particular dimensions and areas creating the research phenomena.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 9, s. 29-44
Keywords: sustainable development; innovation; competitiveness; relationships